2004
DOI: 10.1111/j.1365-2222.2004.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory allergy to peach leaves and lipid‐transfer proteins

Abstract: Pru p 3 from peach leaves can act as a respiratory allergen and cause occupational rhinoconjunctivitis and asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…Interestingly we also found similar levels of expression for Pru p 3.03 and Pru p3.01, indicating that both might be involved in peach pollen allergy. A similar amount of LTP (Mal d 3) in peach leaf and fruit skin has been previously reported (GarcÌa et al 2004), and our results show that two isoallergens Pru p 3.01 and Pru p 3.02 might be present.…”
Section: Predominant Isoallergens Involved In Peach Allergysupporting
confidence: 83%
“…Interestingly we also found similar levels of expression for Pru p 3.03 and Pru p3.01, indicating that both might be involved in peach pollen allergy. A similar amount of LTP (Mal d 3) in peach leaf and fruit skin has been previously reported (GarcÌa et al 2004), and our results show that two isoallergens Pru p 3.01 and Pru p 3.02 might be present.…”
Section: Predominant Isoallergens Involved In Peach Allergysupporting
confidence: 83%
“…1). We used intranasal routes instead of oral for several reasons: (i) dose of protein needed13, (ii) the intrinsic tolerogenic capacity of the gastrointestinal route161730 and (iii) the capacity of Pru p 3 to sensitise patients through inhalation313233343536. One week after the final sensitisation, all mouse groups (including untreated mice) were challenged with Pru p 3 (100 μg) by intraperitoneal injection.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of peach allergy, although it has been associated with the oral and gastrointestinal routes, some authors found a limited IgE antibody response that could be the consequence of the tolerance mechanisms associated with these routes1617. Moreover, food allergic reactions may also develop following airborne sensitisation and/or challenge, as shown by Pru p 3 which can sensitise patients through both the oral and inhalational routes313233343536.…”
Section: Discussionmentioning
confidence: 99%
“…Lombardero and co-workers suggested that in some patients primary sensitization occurs against Art v 3, a LTP present in mugwort pollen [38], although others concluded that such sensitization follows peach sensitization [39]. Sensitization via the inhalation of Pru p 3 derived from peach leaves has been suggested to precede the clinical expression induced by the allergen via the oral route [40]. A woman employed in a fruit and vegetable wholesale store developed rhinitis and asthma in the workplace well before becoming allergic to fruits [41].…”
Section: Evidence For Adult Extra-intestinal Sensitization To Food Almentioning
confidence: 99%